Carbonized composite cementing material as well as preparation method and application thereof
By using carbonized composite gelling materials, using fly ash, slag powder and calcium carbide slag powder, and forming highly reactive gelling substances through carbonization activation, the problems of high cost and environmental pollution of existing underground filling materials are solved, and the low-cost and environmentally friendly underground filling effect is achieved, and carbon dioxide emissions are effectively reduced.
Patent Information
- Application Number
- CN202411577073.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
AI Technical Summary
The existing underground filling materials are costly and environmentally polluted, making it difficult to effectively utilize industrial solid waste and cannot effectively reduce carbon dioxide emissions.
Carbonized composite cementitious material is used, which consists of fly ash, slag powder, calcium carbide slag powder and carbon dioxide. The slag powder and calcium carbide slag powder are activated through the carbonization process to form a highly reactive gelling substance to replace traditional cement materials.
It has achieved low-cost and environmentally friendly underground filling materials, which can effectively absorb industrial solid waste, fix carbon dioxide, reduce the use of cement materials, and thus reduce carbon dioxide emissions.
Smart Images

Figure CN119528464A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization and green underground filling materials, and specifically relates to a carbonized composite gelling material and a preparation method and application thereof. Background Art
[0002] The mining process of underground resources such as coal, oil and gas will form underground voids, cracks and goaf areas, which will not only affect the integrity and stability of the rock formation, leading to oil and gas leakage and even geological subsidence, but also damage the ecological environment around the mining area and cause environmental pollution. Reserving coal pillars is a common method used in the process of coal mining to prevent the collapse of goaf areas, but it still cannot avoid affecting the integrity and stability of the rock formation, leading to oil and gas leakage and even geological subsidence, and will also cause a large amount of coal resources to be wasted. At present, by injecting filling cementitious materials into underground cracks or goaf areas, a stable mechanical structure is formed in the underground area, which can prevent the surrounding rock formations from becoming unstable in the underground goaf area, and then realize the filling, reinforcement and stable sealing of the underground goaf area, which is of great significance to the safe mining of underground resources.
[0003] In recent years, with the increasing demand for underground backfill in underground resource mining industries such as coal, oil and gas, the development of low-cost, high-performance filling materials has gradually become the focus of researchers. Most of the existing filling materials are made of cement and solid waste. Although a certain strength is guaranteed, cement has a high raw material cost. At the same time, a large amount of coal-based solid waste such as fly ash will be generated during coal mining. The accumulation of a large amount of solid waste will not only waste resources, but also occupy a large amount of arable land, causing soil and groundwater pollution. The comprehensive resource utilization of solid waste is imperative. More importantly, with the in-depth development of the concept of low-carbon environmental protection, my country's high-emission industries such as coal-fired power have shown great demand in carbon reduction, carbon fixation, and replacement of backfill materials in mine goafs. The technology of carbonization of industrial solid waste (referred to as solid waste) by carbonization of carbon dioxide (CO2) has also ushered in a rapid development trend. By efficiently utilizing solid waste, we will focus on building a clean, low-carbon, safe and efficient mine production system, which provides opportunities for the development and application of CO2 carbonization coupled solid waste-based mine filling materials. Summary of the invention
[0004] In view of the above-mentioned prior art, the present invention provides a carbonized composite cementitious material and a preparation method and application thereof, which has the characteristics of low cost, strong environmental friendliness and resource recycling. This method can not only fully absorb industrial solid waste and realize the fixed storage of carbon dioxide, but also realize the replacement of cement materials and reduce carbon dioxide emissions.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: to provide a carbonized composite cementitious material, the raw materials for preparation include base material, water and CO2, the base material includes the following components in parts by mass: 20 to 90 parts of fly ash, 5.5 to 45 parts of slag powder and 4.5 to 55 parts of calcium carbide slag powder; the mass ratio of water to base material is 0.5:1, and the ratio of CO2 to base material is 1.7L:1kg.
[0006] The beneficial effects of the above technical scheme adopted in the present invention are: the main component of the fly ash adopted in the present invention is aluminosilicate, which is a low-activity glassy structural material; the main component of the slag powder adopted is aluminosilicate, which is a high-activity glassy structural material that can be activated during the carbonization process; the carbide slag powder adopted is the alkali activator and main carbon fixer of the system, and its main components are calcium hydroxide and calcium carbonate. During the use of carbonized composite cementitious materials, carbide slag alkali-excites blast furnace slag to generate cross-linked calcium silicate hydrate (CSH). The carbonized calcium carbonate fills the CSH pores in the cementitious system, provides nucleation sites and plays a dilution effect, thereby promoting the alkali-excitation reaction. The slag powder can more easily undergo alkali-excitation reaction after carbonization and activation. Fly ash has a micro-aggregate effect and can effectively fill the pores of the hydration products, making the hydration products tightly connected. At the same time, it replaces part of the free water in the pores of the hydration products, improves the fluidity of the slurry, and also increases the later strength of the slurry. CO2 reacts with calcium oxide or calcium hydroxide in carbide slag, and while fixing carbon, it will generate calcium carbonate, which can be filled into the CSH structure. At the same time, it can also promote the reaction of a small amount of calcium silicate in the slag to generate CSH. Under the joint action of the preparation raw materials, the carbonized composite cementitious material can effectively exert the material properties, and the performance will not be reduced due to the lack of cement clinker powder.
[0007] Based on the above technical solution, the present invention can also be improved as follows.
[0008] Furthermore, the carbonized composite cementitious material has a base material comprising the following components in parts by mass: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of carbide slag powder.
[0009] Furthermore, the average particle size of fly ash is 40 to 50 μm.
[0010] Furthermore, the average particle size of the slag powder is 20 to 30 μm.
[0011] Furthermore, the average particle size of the carbide slag powder is 55-65 μm, and the content of calcium hydroxide is greater than 60%.
[0012] Furthermore, the preparation method of the carbonized composite gelled material comprises the following steps:
[0013] (1) Mechanical treatment: crushing carbide slag and blast furnace slag to obtain carbide slag powder and slag powder;
[0014] (2) Raw material mixing and slurry preparation: carbide slag powder, slag powder and fly ash are mixed evenly to obtain a base material, and water is added to form a slurry;
[0015] (3) Preparation of carbonized composite gelled material: CO2 is introduced into the slurry at room temperature and pressure under stirring conditions, with a total amount of 1.7 L of CO2 introduced based on 1 kg of base material; the stirring speed is 350-450 r / min, thereby obtaining a carbonized composite gelled material.
[0016] Furthermore, in step (3), CO2 gas having a volume concentration of 10% to 99.5% is introduced into the slurry, and the ventilation and stirring time is 10 to 100 minutes.
[0017] Furthermore, CO2 gas with a volume concentration of 99.5% was introduced into the slurry, and the ventilation and stirring time was 10 minutes.
[0018] Furthermore, in step (3), the stirring speed is 400 r / min.
[0019] Furthermore, the carbonized composite gelling material is used to prepare roadbed filling material or mine filling material.
[0020] The beneficial effect of the above-mentioned further technical scheme adopted in the present invention is that the blast furnace slag powder can provide the system with a Ca, Si, Al, O network structure with volcanic ash activity. After carbonization activation, the bonds are broken and reorganized under the alkaline conditions of calcium carbide slag to generate CSH, calcium aluminate hydrate (CAH) or calcium aluminosilicate hydrate (CSAH) cementitious materials. At this time, the fly ash and calcium carbonate in the system can be quickly filled in these network structures, exerting a synergistic effect to provide strength for the composite cementitious system.
[0021] The beneficial effects of the present invention are:
[0022] (1) The carbonized composite cementitious material of the present invention has high reactivity, can replace the traditional cementitious material and be applied to the filling of roadbed and mine, and effectively provide the system with cementitious activity;
[0023] (2) The carbonized composite cementitious material of the present invention can utilize industrial solid waste and has the characteristics of strong applicability, low cost, strong environmental friendliness, and resource recycling;
[0024] (3) The carbonized composite cementitious material of the present invention can bind CO2 while ensuring strength, effectively realizing the fixation and storage of carbon dioxide, with a carbon fixation rate of about 3%;
[0025] (4) The carbonized composite cementitious material of the present invention has good transport performance and can meet the requirements of longer distance transport during the filling process; the setting time of the carbonized composite cementitious material is reduced, the initial setting time is greater than 480 minutes, and the final setting time is less than 640 minutes, which is shortened by an average of 160 minutes, avoiding the use of early setting agents, thereby reducing the preparation cost; the water bleeding rate is reduced, and the material stability is enhanced; the slump is increased, and the micro-slump value of the material is greater than 120 mm.
[0026] (5) The carbonized composite cementitious material of the present invention can realize a significant improvement in the strength of the composite cementitious material, especially the early strength, after carbonization, which is difficult to achieve by using only carbide slag as alkali activation. Carbide slag activated slag and fly ash can often only guarantee the later strength. The 3-day compressive strength of the carbonized composite cementitious material is 5.56 MPa, which is a relative increase of 67.47% compared with 3.32 MPa before carbonization. The 28-day compressive strength is 21.46 MPa, which is a relative increase of 17.85% compared with 18.21 MPa before carbonization. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart for the preparation of carbonized composite cementitious materials. DETAILED DESCRIPTION
[0028] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0029] Example 1
[0030] A carbonized composite cementitious material includes the following base materials by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of calcium carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 1.7L; the preparation flow chart is as follows Figure 1 As shown, the specific preparation steps are as follows:
[0031] (1) Mechanical treatment: The carbide slag and blast furnace slag are crushed by a jaw crusher, then ground by a ball mill, and the ball milled particles are screened by an electric vibrating screen to obtain carbide slag powder and slag powder; wherein the average particle size of the carbide slag powder is about 60 μm; the average particle size of the slag powder is about 25 μm; and the average particle size of the fly ash used is 45 μm;
[0032] (2) Mixing and slurrying of raw materials: Mix the formulated amount of carbide slag powder, slag powder and fly ash in a blender to obtain a base material; take 1 kg of the base material, add water and stir to form a slurry in a mass ratio of water to base material of 0.5:1;
[0033] (3) Preparation of carbonized composite cementitious material: Under normal temperature and pressure and stirring conditions, industrial flue gas with a CO2 volume concentration of 99.5% is introduced into the slurry at a ventilation rate of about 10 L / h, a ventilation and stirring time of 10 min, and a stirring speed of 400 r / min to obtain a carbonized composite cementitious material.
[0034] Example 2
[0035] A carbonized composite cementitious material comprises the following base materials in parts by weight: 52 parts of fly ash, 28 parts of slag powder, and 20 parts of carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 1.7L; the specific preparation steps are the same as those in Example 1.
[0036] Example 3
[0037] A carbonized composite cementitious material comprises the following base materials in parts by weight: 64 parts of fly ash, 21 parts of slag powder, and 15 parts of carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 1.7L; the specific preparation steps are the same as those in Example 1.
[0038] Example 4
[0039] A carbonized composite cementitious material comprises the following base materials in parts by weight: 76 parts of fly ash, 14 parts of slag powder, and 10 parts of carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 1.7L; the specific preparation steps are the same as those in Example 1.
[0040] Example 5
[0041] A carbonized composite cementitious material comprises the following base materials in parts by weight: 88 parts of fly ash, 7 parts of slag powder, and 5 parts of carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 1.7L; the specific preparation steps are the same as those in Example 1.
[0042] Example 6
[0043] A carbonized composite gelling material, whose raw materials and usage are the same as those in Example 1; during the preparation process, industrial flue gas with a CO2 volume concentration of 50% is introduced in step (3), the stirring time is 20 minutes, and the remaining steps are the same as those in Example 1.
[0044] Example 7
[0045] A carbonized composite gelling material, whose raw materials and usage are the same as those in Example 1; during the preparation process, industrial flue gas with a CO2 volume concentration of 10% is introduced in step (3), the stirring time is 100 minutes, and the remaining steps are the same as those in Example 1.
[0046] Application Examples
[0047] The method for using the carbonized composite gelling material obtained in the above-mentioned embodiments 1 to 7 as a roadbed filling material or a mine filling material is as follows:
[0048] (1) Mine: The obtained carbonized composite cementitious material is transported to the goaf and cracks through a delivery pump;
[0049] (2) Roadbed: The obtained carbonized composite cementitious material is mixed with sand and gravel, stirred for 120 seconds, paused for 20 seconds, and then stirred for 120 seconds, and then used for filling the roadbed.
[0050] Comparative Example 1
[0051] A composite cementitious material includes the following base materials in parts by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of carbide slag powder; the specific preparation steps are as follows:
[0052] (1) Mechanical treatment: The carbide slag and blast furnace slag are crushed by a jaw crusher, then ground by a ball mill, and the ball milled particles are screened by an electric vibrating screen to obtain carbide slag powder and slag powder; wherein the average particle size of the carbide slag powder is about 60 μm; the average particle size of the slag powder is about 25 μm; and the average particle size of the fly ash used is 45 μm;
[0053] (2) Mixing and slurrying of raw materials: Mix the formulated amount of carbide slag powder, slag powder and fly ash in a blender to obtain a base material; take 1 kg of the base material, add water and stir to form a slurry in a mass ratio of water to base material of 0.5:1;
[0054] (3) Preparation of composite cementitious material: Stirring the slurry at room temperature and pressure at a stirring speed of 400 r / min for 10 min to obtain a composite cementitious material.
[0055] Comparative Example 2
[0056] A composite cementitious material comprises the following base materials in parts by weight: 52 parts of fly ash, 28 parts of slag powder, and 20 parts of carbide slag powder; the specific preparation steps are the same as those of comparative example 1.
[0057] Comparative Example 3
[0058] A composite cementitious material comprises the following base materials in parts by weight: 64 parts of fly ash, 21 parts of slag powder, and 15 parts of carbide slag powder; the specific preparation steps are the same as those in Example 1.
[0059] Comparative Example 4
[0060] A composite cementitious material comprises the following base materials in parts by weight: 76 parts of fly ash, 14 parts of slag powder, and 10 parts of carbide slag powder; the specific preparation steps are the same as those of comparative example 1.
[0061] Comparative Example 5
[0062] A composite cementitious material comprises the following base materials in parts by weight: 88 parts of fly ash, 7 parts of slag powder, and 5 parts of carbide slag powder; the specific preparation steps are the same as those of comparative example 1.
[0063] Comparative Example 6
[0064] A carbonized composite cementitious material comprises the following base materials in parts by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of calcium carbide slag powder; the total amount of CO2 introduced per kilogram of base material is approximately 0.85L; during the preparation process, the ventilation and stirring time in step (3) is 5 minutes, and the remaining steps are the same as in Example 1.
[0065] Comparative Example 7
[0066] A carbonized composite cementitious material comprises the following base materials in parts by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of calcium carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 3.4L; during the preparation process, the ventilation and stirring time in step (3) is 20 minutes, and the remaining steps are the same as in Example 1.
[0067] Comparative Example 8
[0068] A carbonized composite cementitious material comprises the following base materials in parts by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of calcium carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 5.1L; during the preparation process, the ventilation and stirring time in step (3) is 30 minutes, and the remaining steps are the same as in Example 1.
[0069] Comparative Example 9
[0070] A carbonized composite cementitious material comprises the following base materials in parts by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of calcium carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 6.8L; during the preparation process, the ventilation and stirring time in step (3) is 40 minutes, and the remaining steps are the same as in Example 1.
[0071] Comparative Example 10
[0072] A carbonized composite cementitious material comprises the following base materials in parts by weight: 40 parts of fly ash, 35 parts of slag powder, and 25 parts of calcium carbide slag powder; the total amount of CO2 introduced per kilogram of base material is 8.5L; during the preparation process, the ventilation and stirring time in step (3) is 50 minutes, and the remaining steps are the same as in Example 1.
[0073] Experimental example
[0074] (1) Slump test: A micro-slump cone with a height of 150 mm, a bottom diameter of 100 mm, and a top diameter of 50 mm was used; the composite cementitious material slurry was loaded into the slump cone in three layers, with 1 / 3 of the slump cone filled each time; after the slump cone was filled, the micro-slump cone was lifted vertically at a constant speed, and the composite cementitious material slurry would slide down under the action of gravity. The difference between the initial height and the final height of the composite cementitious material slurry was measured as the slump.
[0075] (2) Setting time test: The setting time of the composite cementitious material slurry was measured using an ISO Vicat instrument in accordance with ASTM C150. During the test, a needle was placed close to the surface of the prepared composite cementitious material slurry. The remaining height of 5 mm was recorded as the initial setting time, and when the needle only dropped 0.5 mm, it was the final setting time.
[0076] (3) Strength test: The compressive strength test was carried out in accordance with GB / T50081-2016 Standard for Test Methods for Mechanical Properties of Ordinary Concrete. The composite cementitious material slurry was poured into a mold coated with a lubricant, compacted and the excess slurry on the surface was scraped off. The slurry was placed in an environment of 18-22°C and 90-95% RH for curing for 24-48 h, demolded, and cured for 3, 7, and 28 d, respectively, to obtain test blocks for strength testing.
[0077] (4) Water seepage rate test: Use a 50 mL beaker to add the prepared composite cementitious material to the 50 mL mark, and cover the mouth of the beaker with plastic wrap to prevent water evaporation. Use a pipette to absorb the water precipitated on the surface every 10 min until no obvious water precipitates in the beaker, and measure the total content of the absorbed water.
[0078] Test results:
[0079] 1. The physical properties and chemical compositions of fly ash powder, slag powder and carbide slag powder were measured. The results are shown in Table 1 and Table 2.
[0080] Table 1 Physical properties of each component
[0081]
[0082] Table 2 Chemical composition of each component (%)
[0083]
[0084] As can be seen from Table 2, the content of SiO2 in fly ash reaches 45%, and the content of Al2O3 reaches 24%, and the content of the two is as high as 69%. The content of CaO in slag powder reaches 39%, the content of SiO2 reaches 33%, and the content of Al2O3 reaches 15%, and the content of the three is as high as 87%, mainly aluminosilicate. The main chemical component of carbide slag powder is CaO, and its content is as high as 67.95%. After thermogravimetric treatment, it is calculated that the calcium hydroxide content is greater than 60%.
[0085] 2. The apparent carbon fixation amount of the composite cementitious materials prepared in Example 1 and Comparative Examples 6 to 10 was tested. Calcium carbonate will decompose at 550 to 900°C to cause mass loss. The weight loss of carbonized regenerated micropowder in the range of 550 to 900°C was tested by pyrolysis method as the CO2 fixation amount. The mass loss of carbonate decomposition was normalized according to the initial powder mass. The apparent carbon fixation amount of Example 1 was calculated to be 3.1%, and the apparent carbon fixation amounts of Comparative Examples 6 to 10 were 1.9%, 4.3%, 4.7%, 4.9%, and 5.5%; the longer the reaction time, the higher the carbon fixation rate.
[0086] 3. The composite cementitious materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to slump tests according to the National Standardization Committee GB / T50080 standard. The slump of the composite cementitious materials prepared in Examples 1 to 5 is greater than that in Comparative Examples 1 to 5, specifically, the slumps of Examples 1 to 5 are 124 mm, 129 mm, 133 mm, 137 mm, and 139 mm, respectively; the slumps of Comparative Examples 1 to 5 are 121 mm, 125 mm, 130 mm, 134 mm, and 137 mm, respectively. This is because CO2 reacts with part of the carbide slag, resulting in a weakened absorption effect of the carbide slag on water, which increases the slump. At the same time, in the initial stage of the reaction, the content of the carbide slag has a dominant influence. The less carbide slag, the less gelling material generated in the initial stage of the reaction, the sparser the gelling network structure formed, the weaker the displacement restriction on the material, and the greater the slump.
[0087] 4. The composite cementitious materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to a setting time test, and the setting time of the composite cementitious material slurry was measured using an ISO Vicat instrument according to the ASTM C150 standard. The results are shown in Table 3. The setting time of the material is of great significance in construction. The initial setting time should not be too short, and the final setting time should not be too long.
[0088] Table 3 Test results of setting time of composite cementitious materials
[0089]
[0090] It can be seen from the results in Table 3 that the initial setting time and final setting time of the composite cementitious materials prepared in Examples 1 to 5 are shorter than those in Comparative Examples 1 to 5. This is because CO2 reacts with part of the carbide slag to generate calcium carbonate, which promotes the hydration of the system and generates a CSH structure, accelerates the loss of plasticity and generates strength of the material system. Since the transportation time of the material for underground filling under normal circumstances exceeds 120 minutes, a longer initial setting time and a shorter final setting time are required. When Comparative Examples 1 to 5 are not subjected to mineralization treatment, the material setting time is much greater than the demand, which leads to the need to add an early setting agent to shorten the setting time. After the CO2 mineralization treatment is introduced into the present invention, part of the carbide slag in the system is consumed, resulting in the weakening of the alkali excitation effect of the carbide slag on fly ash and slag powder, shortening the initial setting time and final setting time, and significantly enhancing the early mechanical properties of the system. By introducing the CO2 mineralization process, the initial setting time and final setting time can be shortened by an average of 160 minutes, avoiding the use of early setting agents, thereby reducing the preparation cost.
[0091] 5. The composite cementitious materials prepared in Example 1 and Comparative Example 1 were tested for water seepage rate. The results showed that the water seepage rates of Example 1 and Comparative Example 1 were 10.2% and 7.4%, respectively. It can be seen that the water seepage rate was significantly reduced after the introduction of CO2 mineralization treatment, indicating that after CO2 reacted with carbide slag, the generated calcium carbonate could quickly form a gel structure with hydrated calcium silicate, calcium sulfonate, etc., thereby fixing part of the water. In the composite cementitious material system, the water seepage rate is an important indicator of transportation performance and is often used to reflect the stability of the slurry. When the water seepage rate is too large, the filling material is prone to obvious segregation and precipitation during transportation, thereby causing pipeline blockage accidents.
[0092] 6. The compressive strength test of the composite cementitious material test blocks prepared in Examples 1 to 5 and Comparative Examples 1 to 10 was conducted at 3d, 7d and 28d of curing, and the results are shown in Table 4. From the results in Table 4, it can be seen that the 3d, 7d and 28d strength of the composite cementitious material test blocks prepared in Examples 1 to 5 and Comparative Examples 1 to 5 gradually decreases with the increase of fly ash content, specifically, the 3d, 7d and 28d strength of Example 1 gradually decreases from 5.56, 12.21 and 21.46 MPa to 0.29, 1.02 and 3.22 MPa of Example 5. This is because the strength of the material is mainly provided by the alkali-activated product generated by the alkali-activated reaction between slag powder and carbide slag powder. As the fly ash content increases, the content of slag powder and carbide slag powder decreases, the generated alkali-activated product decreases, and the strength of the material deteriorates.
[0093] Comparing Example 1, Example 6 and Example 7, under the condition of a certain total amount of CO2 and the ventilation rate of this experiment, changing the CO2 concentration and the ventilation time has no obvious change on the strength of the material.
[0094] Compared with Examples 1, 3-5 and Comparative Examples 1, 3-5, the 3d, 7d and 28d strengths of Examples 1, 3-5 are all relatively high, among which the 3d strength is the most significant, specifically, the 3d, 7d and 28d strengths of Example 1 are 5.56, 12.21 and 21.46 MPa, which are 67.47%, 12.02% and 17.85% higher than the 3.32, 10.9 and 18.21 of Comparative Example 1. CO2 mineralization treatment has a good promoting effect on the development of mechanical properties of the filling cementitious material system as a whole. This is because the blast furnace slag in the system can generate products such as hydrated calcium silicate and calcium aluminate more quickly after the CO2 mineralization activation process, and the calcium carbonate generated by mineralization has a certain pore filling effect, which can make the material more compact and make the compressive strength of the material system higher. The early strength has a more significant improvement because when the early gel structure is not tight, the pore filling support effect of the calcium carbonate generated by mineralization is more obvious, so that the strength improvement is more significant.
[0095] Compared with Example 2 and Comparative Example 2, the strengths of 3d and 7d are consistent with the comparative relationship of the above-mentioned embodiments, but the strength of 28d of Example 2 is lower than that of Comparative Example 2. This is because under this ratio system, the negative effect of mineralization consuming carbide slag and reducing the formation of alkali-excited products is greater than the above-mentioned positive effect, thereby lowering the strength.
[0096] Compared with Example 1 and Comparative Examples 6 to 10, the 3d strength fluctuates and rises as the reaction time increases; the 7d and 28d strengths first increase and then decrease as the reaction time increases, reaching a peak value when the reaction time is 10 min and the carbon fixation rate is 3.1%, that is, Example 1. Specifically, the 3d, 7d and 28d strengths of Example 1 are 5.56, 12.21 and 21.46 MPa.
[0097] Table 4 Compressive strength test results of composite cementitious materials after curing
[0098]
[0099]
[0100] To sum up, the optimal CO2 ventilation volume in the present invention is 1.7L of total CO2 introduced per kilogram of base material. At this time, the carbonized composite cementitious material mixed with fly ash, slag powder and carbide slag powder can completely replace cement while ensuring the fluidity and mechanical properties required for filling, and can also achieve an absorption capacity of 7 kg CO2 / ton of cementitious material under strength conditions. It is a high-performance, low-cost all-solid waste carbonized filling cementitious material that can achieve multiple goals of solid waste management, CO2 emission reduction and effective filling of underground voids.
[0101] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A carbonized composite cementitious material, characterized in that: The prepared raw materials include base material, water and CO2. The base material includes the following components in parts by mass: 20 to 90 parts of fly ash, 5.5 to 45 parts of slag powder and 4.5 to 55 parts of carbide slag powder; the mass ratio of the water to the base material is 0.5:1, and the ratio of CO2 to the base material is 1.7L:1kg.
2. The carbonized composite cementitious material according to claim 1, characterized in that: The base material comprises the following components in parts by mass: 40 parts of fly ash, 35 parts of slag powder and 25 parts of carbide slag powder.
3. The carbonized composite gelled material according to claim 1 or 2, characterized in that: The average particle size of the fly ash is 40 to 50 μm.
4. The carbonized composite gelled material according to claim 1 or 2, characterized in that: The average particle size of the slag powder is 20 to 30 μm.
5. The carbonized composite gelled material according to claim 1 or 2, characterized in that: The average particle size of the carbide slag powder is 55-65 μm, and the content of calcium hydroxide is greater than 60%.
6. The method for preparing the carbonized composite gelled material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mechanical treatment: crushing carbide slag and blast furnace slag to obtain carbide slag powder and slag powder; (2) Raw material mixing and slurry preparation: carbide slag powder, slag powder and fly ash are mixed evenly to obtain a base material, and water is added to form a slurry; (3) Preparation of carbonized composite gelled material: CO2 is introduced into the slurry at room temperature and pressure under stirring conditions, with a total amount of 1.7 L of CO2 introduced based on 1 kg of base material; the stirring speed is 350-450 r / min, thereby obtaining a carbonized composite gelled material.
7. The method for preparing the carbonized composite gelled material according to claim 6, characterized in that: In the step (3), CO2 gas with a volume concentration of 10% to 99.5% is introduced into the slurry, and the ventilation and stirring time is 10 to 100 minutes.
8. The method for preparing the carbonized composite gelled material according to claim 7, characterized in that: CO2 gas with a volume concentration of 99.5% was introduced into the slurry, and the ventilation and stirring time was 10 minutes.
9. The method for preparing the carbonized composite gelled material according to claim 6, characterized in that: The stirring speed in step (3) is 400 r / min.
10. The use of the carbonized composite cementitious material according to any one of claims 1 to 5, characterized in that: The carbonized composite gelling material is used to prepare roadbed filling material or mine filling material.
Citation Information
Cited By
Mining damage control method for multi-medium carbon pollution cooperative reduction and control and resource application
CN120100514A
Coal-based solid waste cementing material for coal mine filling engineering as well as preparation method and application of coal-based solid waste cementing material
CN120136461A
Coal-based solid waste cementing material for coal mine filling engineering, preparation method and application
CN120136461B
Method for rapidly determining optimal carbonization parameters of calcium-based alkaline material in all-solid waste gelling system under specific mix proportion
CN122117111A